ANALISIS PENERAPAN GREEN ACCOUNTING DITINJAU DARI PROFITABILITAS DAN CORPORATE SOCIAL RESPONBILITY (CSR) PERUSAHAAN - Citra Puspa Salira (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to identify and analyze the application of green accounting in terms of Corporate Social Responsibility (CSR) and profitability, and the profitability variable was measured using ROA. There are two variables in this study which are thought to affect green accounting in energy sub-sector companies listed on the Indonesia Stock Exchange. The population of this study is the energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) 2018-2020. This study uses a sample of 102 energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) which were selected using the purposive sampling method. The data of this study were analyzed using the multiple linear regression analysis method in this study. The results of this study indicate that the profitability variable has an effect on the green accounting of a company. Meanwhile, Corporate Social Responsibility (CSR) has no effect on the green accounting of company.